Analisis Yuridis terhadap Klausul Kerja yang Kontroversial dalam perspektif Hukum Ketenagakerjaan dan Hukum HAM: Studi Kasus PT. Mitra Adi Sentosa - Septia Atma Milanisa (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
This study examines the legality of a clause in the employment agreement of PT. Mitra Adi Sentosa which states that the employment relationship is not subject to the Manpower Act but solely to the provisions of the Indonesian Civil Code (KUHPerdata). This clause raises legal issues as it disregards imperative norms intended to protect the fundamental rights of workers. The aim of this research is to analyze the compatibility of such employment agreement with the principles of contract law, labor law, and human rights. The method used is normative juridical research with a statutory approach. The findings reveal that clauses contradicting the Manpower Act are legally invalid and may endanger worker protection, thereby violating the principles of legality, legal protection, and social justice. This study underscores the importance of upholding the hierarchy of norms, positioning labor law as lex specialis and human rights as lex superior in employment contracts, and advocates for the drafting of fair and lawful employment agreements as a means of protecting the weaker party in industrial relations.